2011
DOI: 10.1080/08957959.2011.565057
|View full text |Cite
|
Sign up to set email alerts
|

High pressure-assisted encapsulation of vitamin D2in reassembled casein micelles

Abstract: For the encapsulation of vitamin D 2 , native casein micelles and vitamin D 2 with or without additional Ca 2+ -P i were treated at 600 MPa and 37 • C for 60 min. The pressure release rate was set at 20 or 600 MPa/min. Vitamin D 2 was quantified by reversed-phase high-performance liquid chromatography, and physical properties of the micelles were analysed by photon correlation spectroscopy. The results demonstrate that simultaneous application of Ca 2+ -P i and high pressure treatment with a fast release rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Menendez‐Aguirre et al . () encapsulated vitamin D2 in native CM that were isolated via microfiltration, subsequently spray dried and then disintegrated by high hydrostatic pressure (Post et al ., ; Menendez‐Aguirre et al ., ). However, it cannot be excluded that the structure of CM might be changed as a result of technological processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menendez‐Aguirre et al . () encapsulated vitamin D2 in native CM that were isolated via microfiltration, subsequently spray dried and then disintegrated by high hydrostatic pressure (Post et al ., ; Menendez‐Aguirre et al ., ). However, it cannot be excluded that the structure of CM might be changed as a result of technological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although CM already have a semi-open structure, they must be further treated to make the hydrophobic core accessible for the lipophilic compounds. Menendez-Aguirre et al (2011) encapsulated vitamin D2 in native CM that were isolated via microfiltration, subsequently spray dried and then disintegrated by high hydrostatic pressure (Post et al, 2009;Menendez-Aguirre et al, 2011). However, it cannot be excluded that the structure of CM might be changed as a result of technological processes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, each delivery system must be specifically designed for each application depending on the characteristics of the active agent to be encapsulated, e.g., solubility, physical, and chemical stability. Vitamin D has been encapsulated in numerous systems such as nanoemulsions , nanoparticles , casein micelles , and Poly(D, L)Lactic acid (PLA) nanoparticles prepared from nanoprecipitation method .…”
Section: Introductionmentioning
confidence: 99%
“…The gel strength increased with increasing high-pressure treatment (Johnston et al 1992;Desobry-Banon et al 1994) and a syneresis resistance was observed. Highpressure treatments appear as an interesting tool to entrap different ligands like curcumin, vitamin D 2 , and α-tocopherol (Benzaria et al 2013;Menéndez-Aguirre et al 2011;Chevalier-Lucia et al 2011). It increases the binding constant of these compounds to casein micelles.…”
Section: High Pressurementioning
confidence: 99%